2010
DOI: 10.1111/j.1475-1313.2010.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Objective vs subjective measures of fixation disparity for short and long fixation periods

Abstract: Subjective fixation disparity explained only about 25% of the inter-individual variability in objective fixation disparity. The discrepancy between these two measures might be explained by sensory shifts in retinal correspondence, also in the present condition without forced vergence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 49 publications
4
41
0
Order By: Relevance
“…13 During monocular calibration of the eye movement recordings, binocular measures were stored while only one eye was fixated on the target. The resulting vergence angle without a fusion stimulus is known as heterophoria 24 (values included in Table 1).…”
Section: Orthoptic Examinationmentioning
confidence: 99%
“…13 During monocular calibration of the eye movement recordings, binocular measures were stored while only one eye was fixated on the target. The resulting vergence angle without a fusion stimulus is known as heterophoria 24 (values included in Table 1).…”
Section: Orthoptic Examinationmentioning
confidence: 99%
“…This correlation was also confirmed by objective measures. 22 2. Fixation disparity also correlates with binocular nonius bias.…”
Section: (2)mentioning
confidence: 99%
“…14,24 Dynamic vergence step responses (both convergent and divergent) and heterophoria (during monocular calibration before and after each recording) were measured objectively using an eye-tracking system (EyeLink II; SR Research; Mississauga, Ontario, Canada), at 500 Hz, in the pupillary tracking mode. 22,24 The vergence stimuli were within the 40°horizontal gaze-tracking range. Despite the high physical precision of the system, its practical reliability is limited by the stability of head position: test-retest correlations of vergence velocity among different sessions were between 0.62 and 0.91; regarding the difference between velocity measures between two sessions, the range of Ϯ1.96 SD was Ϯ2.23 deg/s and Ϯ1.02 deg/s for the convergent and divergent velocity, respectively, as found in Bland-Altman plots (not shown).…”
Section: Stimulus and Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that anomalous retinal correspondence in constant strabismus reflects a remapping of the deviated eye onto primary visual cortex 1 . It has also been suggested that sensory shifts in retinal correspondence can occur in normal human subjects 66–68 …”
Section: Relationship To Anti‐diplopic Mechanisms In Other Conditionsmentioning
confidence: 99%